2015
DOI: 10.1111/tbed.12325
|View full text |Cite
|
Sign up to set email alerts
|

Sheep as a Potential Source of Bovine TB: Epidemiology, Pathology and Evaluation of Diagnostic Techniques

Abstract: Bovine tuberculosis (TB) infection is infrequently diagnosed in sheep. Most reports are from single individual cases or flock outbreaks. However, in Spain several outbreaks have been reported recently, all of which had epidemiological links with TB-infected cattle herds. A total of 897 sheep suspected of being infected with TB and belonging to 23 flocks cohabiting with TB-infected cattle herds and/or goats were tested between 2009 and 2013 in Galicia (north-western Spain), using pathological, immunological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 34 publications
6
58
1
Order By: Relevance
“…Macroscopically, lesions in all infected lambs consisted of the typical granulomatous caseous necrotizing lesions in the lung and associated LNs that are usually found in natural cases of TB [5]. The presence of large necrotic coalescing lesions found in unvaccinated control lambs indicated a fast progression of the infection to active TB, similar to what occurs in goats [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroscopically, lesions in all infected lambs consisted of the typical granulomatous caseous necrotizing lesions in the lung and associated LNs that are usually found in natural cases of TB [5]. The presence of large necrotic coalescing lesions found in unvaccinated control lambs indicated a fast progression of the infection to active TB, similar to what occurs in goats [21].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe animal TB involves a multi-host system where domestic (cattle and goats) and wildlife (badger, wild boar and red deer) have a relevant role that varies between regions, depending on climate, habitat and husbandry factors [4]. Recent studies have shown that sheep, traditionally considered a rare host for the MTBC, can be part of the multi-species system which may maintain TB in a region, at least in mixed farms where sheep cohabit with TB-infected cattle and/or goats [5]. Given the abundance and widespread distribution of domestic sheep in Europe and elsewhere, that role may have important implications for global animal TB control, particularly since sheep are not routinely subjected to the periodic diagnostic testing within the National Programmes to eradicate bovine TB in many countries where TB is prevalent in cattle or goats [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bovine tuberculosis is well documented in buffaloes (De Garine‐Wichatitsky et al., ; Michel, de Klerk, Gey van Pittius, Warren, & van Helden, 2007) and goats (Cadmus, Adesokan, Jenkins, & van Soolingen, ; Napp et al., ), whereas ovine TB is considered uncommon and poorly studied (Malone, Wilson, Pollock, & Skuce, ; Muñoz Mendoza et al., ; Muñoz‐Mendoza et al., ). However, a case of bTB in a sheep was previously described in Sicily, the strain was spoligotype SB0841 and had MIRU‐VNTR profile 5,4,5,3,3,10,4,4,4,3,6,5 (Marianelli et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine tuberculosis (bTB) and paratuberculosis (PTB) are widespread infectious diseases that affect many domestic [1,2] and wild [3,4] species. The impact of these diseases derives from losses to the livestock industry, especially dairy cattle [5,6], from hunting and wildlife conservation as well as from their recognized (bTB) or suspected (PTB) zoonotic character.…”
Section: Introductionmentioning
confidence: 99%